The Pivotal Role of Catalysis in France: Selected Examples of Recent Advances and Future Prospects. Issue 12 (12th June 2017) - Olivier‐Bourbigou, Hélène; Chizallet, Céline; Dumeignil, Franck; Fongarland, Pascal; Geantet, Christophe; Granger, Pascal; Launay, Franck; Löfberg, Axel; Massiani, Pascale; Maugé, Françoise; Ouali, Armelle; Roger, Anne‐Cécile; et al.
Abstract: The Review describes the most significant results achieved in France in the field of heterogeneous catalysis over the last 10 years and placed in the context of international research. The focus lies on the research conducted in French academic laboratories, often in close collaboration with industrial partners. A wide range of heterogeneous catalysis is covered, including ab initio calculations, biomass conversion, catalytic cracking, catalyst characterization, CO2 conversion, Fischer–Tropsch, pollution abatement, power‐to‐gas and kinetics. Abstract : Allez la France ! The most significant results achieved in France in the field of heterogeneous catalysis over the last 10 years are presented in this Review. A range of topics from biomass conversion through pollution abatement to Fischer—Tropsch.